FRI0116 A high level of clinical response based on composite indices is associated with improved health-related quality of life: analyses from a phase 3 clinical trial in patients with rheumatoid arthritis. (15th June 2017) - Dougados, M; Zhu, B; Tang, AC; Quebe, A; Stoykov, I; Cai, Z; Ishida, M; Gaich, C
Abstract : Background: Rheumatoid arthritis (RA) is a chronic disease associated with inflammatory activity and joint damage that result in disability, pain, and other impairments. The current recommendation is to assess disease activity based on composite indices with objective signs of inflammation (e.g. synovitis, acute phase reactants) and patient's assessment of disease activity. The patient's perception of disease impact and its treatment also facilitate shared decision-making about treatment. Objectives: To compare patient-reported outcomes (PROs) for RA patients who achieved low disease activity (LDA) or remission based upon the DAS28-ESR compared to those with moderate and high disease activity (MDA and HDA) in this post-hoc analysis of a randomized, double-blind phase 3 clinical trial, RA-BEAM 1 . Methods: 1305 patients were randomized to placebo (N=488), adalimumab (N=330) or baricitinib 4 mg (N=487). Patients with observed DAS28-ESR values at Week 24 (N=1, 010) were divided into 4 disease activity groups: HDA (DAS28-ESR>5.1), MDA (3.2<DAS28-ESR≤5.1), LDA (2.6≤DAS28-ESR≤3.2), or remission (DAS28-ESR<2.6). Change from baseline to Week 24 were assessed for the pain visual analogue scale (VAS, 0–100 mm), Health Assessment Questionnaire-Disability Index (HAQ-DI) and SF-36 physical and mental component score (PCS and MCS) for the intent-to-treat (ITT) patients. Results: Patients with HDA and MDA at Week 24 had greater baseline pain and HAQ-DI scores and lower PCS and MCS scores than patients achieving LDA or remission at Week 24. Lower disease activity at Week 24 was associated with improvement in pain, HAQ-DI, SF-36 PCS and MCS at Week 24. Among patients who achieved remission, residual pain was observed, with close to 40% still experiencing some level of pain and 20% of patients in remission at Week 24 had a residual pain score>20. Sensitivity analyses using other clinical measures (DAS28-CRP, SDAI, CDAI) to define disease activity confirmed the findings. Conclusions: Improving patient disease activity is associated with improved health-related quality of life. Patients who achieved remission had greater improvement in PROs but residual pain remained. Further research is needed to understand the treatment differences in the association between disease activity and PROs among different therapies. References: Taylor PC, Keystone E, van der Heijde D, et al. Baricitinib Versus Placebo or Adalimumab in Patients with Active Rheumatoid Arthritis (RA) and an Inadequate Response to Background Methotrexate Therapy: Results of a Phase 3 Study. Arthritis Rheum 2015;67(Suppl 10):3928. Disclosure of Interest: M. Dougados Grant/research support from: Abbvie, Pfizer, Eli Lilly and Company, Novartis, UCB, Merck, Roche, BMS, Consultant for: Abbvie, Pfizer, Eli Lilly and Company, Novartis, UCB, Merck, Roche, BMS, B. Zhu Employee of: Eli Lilly and Company, A. Tang Employee of: Eli Lilly and Company, A. Quebe Employee of: Eli Lilly and Company, I. Stoykov Employee of: Eli Lilly and Company, Z. Cai Employee of: Eli Lilly and Company, M. Ishida Employee of: Eli Lilly and Company, C. Gaich Employee of: Eli Lilly and Company